RANCANG BANGUN FILLER MACHINE UNTUK PRODUK BERUPA SERBUK KOPI - Addin Naufal Rofif (2024)
Indonesia is one of the largest coffee producers in the world. Many coffee packaging processes still use manual methods. The Vertical Form Fill Seal (VFFS) machine is a machine that can package coffee efficiently. The efficiency comparison between the manual packaging process and the packaging process using machines is very different. The methods used in this research are literature study, concept design process, fabrication process, and trial results. The machine made has dimensions of 500 x 500 x 1700 mm. With several main components, namely hopper, volumetric filler, pipe forming tube, top sealer and bottom sealer. The machine that was made cost Rp 9,470,925.00. This machine has a capacity of 30 sachets per minute. This machine is capable of producing sachet packaging with an average weight of 25 grams.